MENINGKATKAN HASIL BELAJAR PKn MELALUI IMPLEMENTASI KOOPERATIF LEARNING - Sunarti, Ni Nyoman (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
This Classroom Action Research aims to improve student learning outcomes using student learning cooperative learning. The research was carried out in the State Elementary School 3 Mengwi, Badung with the subject of the action of 1 teacher and the recipient of the action subject were 25 grade VI students. This research was conducted in 3 cycles, each cycle using action procedures, namely planning, implementing actions, observing and reflecting. Based on the results of classroom action research on cooperative learning to improve the understanding of fifth grade students of SD No. 1 in the 2015/2016 school year in PKn learning, it was quite effective, which took place in 3 cycles. In the first cycle of student activity 50% of students did not get used to cooperative learning and there were still less interested in discussing. Teacher activity is classified as low with a score of 51.11% and student learning outcomes of 52%, therefore research was conducted in the second cycle with the acquisition of scores on student activities 70% and teacher activities 68.44%, while student learning outcomes in this cycle increased to 76%. Because researchers are not satisfied, there are still students who have not been optimally involved in the process of interaction with the group, so research was conducted in cycle III, with student activity results increasing to 100%, teacher activities becoming 88.44%, and student learning outcomes becoming 100%. From the results of this study it can be concluded that the use of the Cooperative Learning approach can improve PKn learning outcomes of students of ASEAN teaching material at SD No 3 Mengwi. Keywords: Cooperative Learning, PKn